Rescue - Anita Shreve
The car crash should have killed her. But rookie paramedic Peter Webster takes the emergency call, and helps the young woman, Sheila Arsenault, to survive. After the accident, she haunts his thoughts, despite his misgivings about getting involved with a patient. Soon he is embroiled in an intense love affair and in Sheila's troubled life. Eighteen years later, Sheila is long gone and Peter is raising their daughter, Rowan, alone. But Rowan is veering dangerously off course and for the first time in their quiet life together Peter fears for her future. He seeks out the only person who may be able to help Rowan, although Sheila's return is sure to unleash all the questions Peter has been carefully keeping at Why would a mother leave her family? How did the marriage of two people in love unravel?